Subcutaneous terbutaline and control of brittle asthma or appreciable morning dipping. Issue 6432 (9th June 1984) - Ayres, J; Fish, D R; Wheeler, D C; Wiggins, J; Cochrane, G M; Skinner, C
Abstract : In a pilot study two patients with brittle asthma and two with morning dipping received terbutaline or a placebo administered subcutaneously either by continuous infusion or in injections every six hours. In two patients brittle asthma was completely suppressed by terbutaline 1 mg/day given by either method. In the two others early morning dipping responded only to continuous subcutaneous infusions of terbutaline 12 mg/day. Terbutaline administered subcutaneously may be an effective treatment in asthmatic patients who show important diurnal variations in air flow.